Hearing loss and disability exit: measurement issues and coping strategies - Vibeke T. Christensen; Nabanita Datta Gupta; Martin V. Rasmussen (Institute for the Study of Labor (IZA), 2007)
Using unique representative data containing self-reported functional and clinically measured hearing ability for the Danish population aged 50-64, we estimate the effect of hearing loss on receipt of disability benefits accounting for potential endogeneity of functional hearing. Our identification strategy involves simultaneous estimation of labor supply, functional hearing and coping strategies i.e. using assistive devices at work or informing one's employer about the problem. We find that functional hearing disability significantly increases the likelihood of receiving disability benefits for both men and women. Using assistive devices at the work place decreases the likelihood of going on disability for both genders, whereas telling the employer about the disability increases disability-related exit for both genders, but considerably more so for women.
Keywords: J26; 330; Hearing loss; disability exit; functional hearing; clinical audiometry test; gender differences; Alte Menschen; Erwerbsunfähigkeitsrente; Dänemark